Preparation method of novel fluorine-containing pyridine type benzoxazine resin friction layer for droplet nano generator

By combining fluoropyridine-containing benzoxazine resin with two-dimensional carbon nanomaterials, a high-performance friction layer material was prepared, which solved the problems of low conductivity and poor friction characteristics in the droplet nanogenerator, and achieved high Output current and energy density, suitable for energy storage and sensing fields.

CN119119861AActive Publication Date: 2024-12-13INNER MONGOLIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411290110.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-13
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

Common power generation materials in droplet nanogenerators have low conductivity and poor friction characteristics, resulting in unstable output voltage and low output current, and lack of high-performance new power generation materials.

Method used

A fluoropyridine-containing benzooxazine resin is used to combine with two-dimensional carbon nanomaterials, and spray it on the copper electrode sheet to form a friction layer, and gradient curing is used to prepare a high-performance friction layer material.

Benefits of technology

It achieves high output current and high output energy density, has excellent heat resistance, is suitable for energy storage and sensing fields, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119861A_ABST
    Figure CN119119861A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a fluorine-containing pyridine type benzoxazine resin friction layer for a droplet nano generator, and belongs to the technical field of energy materials. The preparation method comprises the following steps: taking 3, 5-difluoro-2, 6-diaminopyridine as an amine source, taking 3, 4, 5-trifluorophenol, 2, 3, 4-trifluorophenol or 2, 4, 5-trifluorophenol as a phenol source, and carrying out condensation reaction on the amine source, the phenol source and paraformaldehyde to synthesize a fluorine-containing pyridine type benzoxazine monomer; and mixing the fluorine-containing pyridine benzoxazine resin with a two-dimensional carbon nanomaterial, performing ultrasonic treatment, spraying on a copper electrode plate, and curing to obtain the fluorine-containing pyridine benzoxazine resin friction layer. The fluorine-containing pyridine type benzoxazine resin friction layer prepared by the method has the characteristics of excellent mechanical property, high temperature resistance, hydrophobic property and the like, and has the advantages of high output current, high energy density and the like when being applied to a droplet nano generator. The invention has the advantages of easily available raw materials, simple preparation process and the like, and has good practicability and wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy materials, and in particular relates to a method for preparing a novel fluorine-containing pyridine-type benzoxazine resin friction layer for a droplet nanogenerator. Background Art

[0002] Water is everywhere in nature, and obtaining mechanical energy from flowing water has always been one of the research focuses. How to extract this energy from water is an unremitting pursuit of people. In addition to using traditional large-scale hydroelectric generators, micro energy harvesting technology-droplet nanogenerators have become a hot topic today, which is of great significance for the development of green energy and solving the energy crisis. Droplet nanopower generation is an emerging technology that aims to generate electricity using the movement of tiny droplets. Compared with traditional hydropower generation, droplet nanopower generation uses the principle of generating charges by the movement of droplets on the surface, and has a more efficient energy conversion efficiency. However, most of the common power generation materials in droplet nanogenerators have challenging problems such as low conductivity and poor friction properties resulting in unstable output voltage and low output current. New power generation materials are urgently needed to be developed.

[0003] Fluorinated pyridine-type benzoxazine is a new type of thermosetting resin with flexible molecular design and good hydrophobicity. The pyridine group can effectively increase the generation and separation efficiency of charges. Two-dimensional carbon nanomaterials can change the energy band structure of the material and optimize the excitation and transmission process of charge carriers. It can be used as a potential material for solid friction layer to reduce friction loss. In this experiment, the material was structurally modified through molecular structure design and functionalization treatment, and a new type of fluorinated pyridine-type benzoxazine resin friction layer was prepared for the study of high-performance droplet nanogenerators. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a fluorinated pyridine-type benzoxazine resin friction layer for a droplet nanogenerator, which has the advantages of readily available raw materials, mild reaction conditions, and simple process.

[0005] Another technical problem to be solved by the present invention is to provide a friction nanogenerator that can be used to generate electrical energy through droplet movement, and the friction nanogenerator has the advantages of high output current, high output energy density, etc.

[0006] In order to achieve the above purpose, the present invention uses 3,5-difluoro-2,6-diaminopyridine as an amine source, 3,4,5-trifluorophenol, 2,3,4-trifluorophenol or 2,4,5-trifluorophenol as a phenol source and polyformaldehyde to carry out condensation reaction to synthesize a fluorine-containing pyridine-type benzoxazine monomer; the prepared fluorine-containing pyridine-type benzoxazine monomer is mixed with a two-dimensional carbon nanomaterial, and after ultrasonic treatment, it is sprayed on a copper electrode sheet, and then placed in an oven for gradient curing to obtain a fluorine-containing pyridine-type benzoxazine resin friction layer;

[0007] The present invention specifically adopts the following specific scheme:

[0008] A method for preparing a fluorinated pyridine-type benzoxazine resin friction layer for a droplet nanogenerator, comprising the following steps:

[0009] Step 1, preparation of fluorinated pyridine-type benzoxazine:

[0010] Adding paraformaldehyde and 3,5-difluoro-2,6-diaminopyridine to an organic solvent, introducing N2 under certain temperature conditions for stirring, then adding a phenol source for reaction, separating the organic solvent after the reaction, washing with alkali, washing with water, and vacuum drying to obtain a product, namely a fluorine-containing pyridine-type benzoxazine monomer; the phenol source is any one of 3,4,5-trifluorophenol, 2,3,4-trifluorophenol or 2,4,5-trifluorophenol;

[0011] The structural formula of the fluorine-containing pyridine-type benzoxazine monomer is as follows:

[0012]

[0013] Wherein, R is one of H, F or CF3.

[0014] The reaction equation is shown in (I):

[0015]

[0016] Wherein, R is one of H, F or CF3.

[0017] Step 2: Preparation of fluorinated pyridine-type benzoxazine resin friction layer material:

[0018] The fluorinated pyridine-type benzoxazine monomer prepared in step 1 and the two-dimensional carbon nanomaterial are mixed in a certain proportion and added to a solvent, and ultrasonically mixed and stirred under certain temperature conditions to obtain a dispersion of the fluorinated pyridine-type benzoxazine and the two-dimensional carbon nanomaterial; the solvent is one of N,N-dimethylformamide, chloroform, acetone, and dimethyl sulfoxide;

[0019] Step 3, preparation of fluorinated pyridine-type benzoxazine resin friction layer:

[0020] The dispersion obtained in step 2 is sprayed on the pre-treated copper electrode sheet, and then placed in an oven for gradient temperature curing. After curing, a composite coating is formed on the copper electrode sheet, and the composite coating is a fluorine-containing pyridine-type benzoxazine resin friction layer.

[0021] Preferably, in step 1, the molar ratio of 3,5-difluoro-2,6-diaminopyridine, phenol source and paraformaldehyde is (0.5-1.5):(3-5):(4-6).

[0022] Preferably, in step 1, the amount of the paraformaldehyde and the organic solvent is in the ratio of 0.4-1.2 g: 20-60 mL; the organic solvent is any one of toluene, dioxane, ethyl acetate or chloroform.

[0023] Preferably, in step 1, the certain temperature condition is 30-60°C, the stirring time is 1-3h; the reaction time is 3-10h; the alkaline washing refers to washing with a NaOH solution with a concentration of 1-3mol / L; the vacuum drying temperature is 80-120°C, and the drying time is 3-8h.

[0024] Preferably, in step 2, the mass ratio of the fluorinated pyridine-type benzoxazine monomer to the two-dimensional carbon nanomaterial is: (50-100):(1-5); the two-dimensional carbon nanomaterial is any one of graphene, graphene oxide, and fluorinated graphene; the amount of the fluorinated pyridine-type benzoxazine monomer to the solvent is 0.1-0.8 g:10-30 mL.

[0025] Preferably, in step 2, the stirring reaction under the certain temperature condition is carried out at a temperature of 20-50° C. and a time of 1-8 h.

[0026] Preferably, in step 3, the pre-treated copper electrode sheet treatment process is: first ultrasonically clean the copper electrode sheet with ethanol for 0.5-2h, and then use a plasma surface treatment instrument to surface treat the copper electrode sheet for 2-8min.

[0027] Preferably, in step 3, the gradient curing is: treating under different gradient temperature conditions with a gradient of 10-30°C, the temperature range is 30°C-170°C; the treatment time under each gradient temperature condition is 1-2h.

[0028] The present invention also provides a use of using the fluorine-containing pyridine benzoxazine resin and the two-dimensional carbon nanomaterial composite coating to prepare a droplet nanogenerator.

[0029] The prepared fluorine-containing pyridine benzoxazine resin and two-dimensional carbon nanomaterial composite coating is used as a friction layer of a droplet nanogenerator to prepare a droplet nanogenerator, and the steps are as follows:

[0030] A copper sheet is used as an electrode sheet; firstly, a fluorinated pyridine-type benzoxazine resin friction layer is pasted on the surface of the electrode sheet, and the friction layer covers the electrode sheet as a whole; then, a copper foil is pasted on a local area of ​​the friction layer to obtain a droplet nanogenerator.

[0031] Test: First, connect the electrode sheet and copper foil to a power source, then add water drops to the surface of the friction layer not covered by the copper foil; the water droplets slide on the surface of the dielectric material and become frictionally charged, resulting in charge separation, thereby generating electrical energy.

[0032] Beneficial effects:

[0033] (1) The present invention designs a series of new fluorinated pyridine-type benzoxazine friction layer materials through molecular scale regulation, which have the advantages of easy acquisition of raw materials, mild reaction conditions, and simple preparation process.

[0034] (2) The droplet nanogenerator prepared by the present invention has excellent heat resistance, high output current, high

[0035] With advantages such as output energy density, it is expected to be applied in the fields of energy storage and sensing and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the infrared spectrum of the fluorinated pyridine-type benzoxazine monomer.

[0037] Figure 2 This is a schematic diagram of the structure of a fluorinated pyridine-type benzoxazine resin-based nanogenerator for a droplet nanogenerator.

[0038] Figure 3 This is a physical picture of the fluorinated pyridine-type benzoxazine resin-based nanogenerator used in droplet nanogenerators.

[0039] Figure 4 Output current diagram of the droplet nanogenerator prepared with a fluorinated pyridine-type benzoxazine resin friction layer. DETAILED DESCRIPTION

[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0041] Unless otherwise specified, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0043] Embodiment 1:

[0044] 0.9 g of paraformaldehyde and 1.5 g of 3,5-difluoro-2,6-diaminopyridine were added to 40 mL of ethyl acetate, N2 was introduced and stirred at 35° C. for 3 h, and then 2.2 g of 3,4,5-trifluorophenol was added and reacted for 6 h. After the organic solvent was separated, the mixture was washed with alkali (using a 3 mol / L NaOH solution for washing), washed with water, and then vacuum dried (80° C., 4 h) to obtain the product, which is a fluorinated pyridine-type benzoxazine monomer with a yield of 85%.

[0045] Infrared spectrum see Figure 1 , 1610cm in the figure -1 The absorption peaks of benzene ring skeleton vibration are 1240 and 1182 cm -1 The absorption peak of C–N–C on the oxazine ring is 1044 cm -1 The symmetrical stretching vibration peak of C–O on the oxazine ring is 937 cm -1 The infrared spectrum shows the characteristic absorption peak of the oxazine ring, and the structural characteristics of the fluorine-containing pyridine-type benzoxazine monomer can be basically determined.

[0046] Then, 0.3 g of 3,4,5-trifluorophenol fluorinated pyridine benzoxazine monomer was mixed with 0.015 g of fluorinated graphene and added to 20 mL of acetone, and stirred at 30 ° C for 3 h to obtain a dispersion of fluorinated pyridine benzoxazine and fluorinated graphene. At the same time, the copper electrode sheet was ultrasonically cleaned with ethanol for 0.5 h, and then the copper electrode sheet was surface treated with a plasma surface treatment instrument for 2 min to obtain a pretreated copper electrode sheet. Finally, the obtained dispersion was sprayed on the pretreated copper electrode sheet, and then placed in an oven for gradient temperature curing, with a gradient curing procedure of 120 ° C for 2 h, 140 ° C for 2 h, 160 ° C for 2 h, and 180 ° C for 2 h. After curing, a composite coating was formed on the copper electrode sheet, which was a fluorinated pyridine benzoxazine resin friction layer.

[0047] The prepared fluorine-containing pyridine benzoxazine resin and two-dimensional carbon nanomaterial composite coating is used as a friction layer of a droplet nanogenerator to prepare a droplet nanogenerator, and the steps are as follows:

[0048] A copper sheet is used as an electrode sheet; first, a fluorinated pyridine-type benzoxazine resin friction layer is pasted on the surface of the electrode sheet, and the friction layer covers the electrode sheet as a whole; then, a copper foil is pasted on a local area of ​​the friction layer to obtain a droplet nanogenerator; the schematic diagram of the droplet nanogenerator is shown in Figure 2 , see the actual picture Figure 3 .

[0049] Test: First, the electrode sheet and copper foil are connected to the power supply through the copper wire, and then a water droplet is added to the friction layer surface not covered by the copper foil using a syringe pump; the water droplet slides on the surface of the dielectric material and is frictionally charged, resulting in charge separation, thereby generating electrical energy. The output current of the droplet nanogenerator is measured, and the output current is shown in Figure 4 The results show that the droplet nanogenerator prepared by the present invention can effectively output current and has achieved remarkable technical results.

[0050] Embodiment 2:

[0051] 1.2g formaldehyde and 0.9g 3,5-difluoro-2,6-diaminopyridine were added to 50mL dioxane, N2 was introduced and stirred at 30°C for 1h, and then 1.5g 2,4,5-trifluorophenol was added and reacted for 4h. After separating the organic solvent, the mixture was washed with alkali (using a 1mol / L NaOH solution) and water, and then vacuum dried (90°C, 5h) to obtain the product, which is a fluorinated pyridine-type benzoxazine monomer with a yield of 80%. Then 0.3g 2,4,5-trifluorophenol fluorinated pyridine-type benzoxazine was mixed with 0.018g graphene oxide and added to 15mL N,N-dimethylformamide, and stirred at 50°C for 5h to obtain a dispersion of fluorinated pyridine-type benzoxazine and graphene oxide. At the same time, the copper electrode sheet was ultrasonically cleaned with ethanol for 1 hour, and then the copper electrode sheet was surface treated with a plasma surface treatment instrument for 3 minutes to obtain a pretreated copper electrode sheet. The obtained dispersion was sprayed on the pretreated copper electrode sheet, and then placed in an oven for gradient curing at 120°C for 2 hours, 140°C for 2 hours, 160°C for 1 hour, and 180°C for 1 hour. After curing, a composite coating was formed on the copper electrode sheet, which was a fluorinated pyridine-type benzoxazine resin friction layer.

[0052] The prepared fluorine-containing pyridine benzoxazine resin and two-dimensional carbon nanomaterial composite coating is used as a friction layer of a droplet nanogenerator to prepare a droplet nanogenerator, and the steps are as follows:

[0053] A copper sheet is used as an electrode sheet; firstly, a fluorinated pyridine-type benzoxazine resin friction layer is pasted on the surface of the electrode sheet, and the friction layer covers the electrode sheet as a whole; then, a copper foil is pasted on a local area of ​​the friction layer to obtain a droplet nanogenerator.

[0054] Embodiment 3:

[0055] 0.4g formaldehyde and 0.3g 3,5-difluoro-2,6-diaminopyridine were added to 10mL dioxane, N2 was introduced and stirred at 30°C for 2h, and then 0.5g 2,4,5-trifluorophenol was added and reacted for 5h. After separating the organic solvent, the mixture was washed with alkali (using a 1mol / L NaOH solution for washing), washed with water, and then vacuum dried (100°C, 3h) to obtain the product, which was a fluorinated pyridine-type benzoxazine monomer with a yield of 80%. Then 0.3g 2,4,5-trifluorophenol fluorinated pyridine-type benzoxazine was mixed with 0.018g graphene oxide and added to 15mL acetone, and stirred at 30°C for 2h to obtain a dispersion of fluorinated pyridine-type benzoxazine and graphene oxide. At the same time, the copper electrode sheet was ultrasonically cleaned with ethanol for 1 hour, and then the copper electrode sheet was surface treated with a plasma surface treatment instrument for 1 minute to obtain a pretreated copper electrode sheet. The obtained dispersion was sprayed on the pretreated copper electrode sheet, and then placed in an oven for gradient curing at 90°C for 1 hour, 120°C for 2 hours, 150°C for 1 hour, and 180°C for 1 hour. After curing, a composite coating was formed on the copper electrode sheet, which was a fluorinated pyridine-type benzoxazine resin friction layer.

[0056] The prepared fluorine-containing pyridine benzoxazine resin and two-dimensional carbon nanomaterial composite coating is used as a friction layer of a droplet nanogenerator to prepare a droplet nanogenerator, and the steps are as follows:

[0057] A copper sheet is used as an electrode sheet; firstly, a fluorinated pyridine-type benzoxazine resin friction layer is pasted on the surface of the electrode sheet, and the friction layer covers the electrode sheet as a whole; then, a copper foil is pasted on a local area of ​​the friction layer to obtain a droplet nanogenerator.

[0058] In summary, the droplet nanogenerator prepared by the present invention has the advantages of excellent heat resistance, high output current, high output energy density, etc., and is expected to be applied in the fields of energy storage and sensing, with broad application prospects.

[0059] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a fluorinated pyridine-type benzoxazine resin friction layer for a droplet nanogenerator, characterized in that: The following steps are involved: Step 1, preparation of fluorinated pyridine-type benzoxazine: Adding paraformaldehyde and 3,5-difluoro-2,6-diaminopyridine to an organic solvent, introducing N2 under certain temperature conditions for stirring, then adding a phenol source for reaction, separating the organic solvent after the reaction, washing with alkali, washing with water, and vacuum drying to obtain a product, namely a fluorine-containing pyridine-type benzoxazine monomer; the phenol source is any one of 3,4,5-trifluorophenol, 2,3,4-trifluorophenol or 2,4,5-trifluorophenol; The structural formula of the fluorine-containing pyridine-type benzoxazine monomer is as follows: Wherein, R is one of H, F or CF3; Step 2: Preparation of fluorinated pyridine-type benzoxazine resin friction layer material: The fluorinated pyridine-type benzoxazine monomer prepared in step 1 and the two-dimensional carbon nanomaterial are mixed in a certain proportion and added to a solvent, and ultrasonically mixed and stirred under certain temperature conditions to obtain a dispersion of the fluorinated pyridine-type benzoxazine and the two-dimensional carbon nanomaterial; the solvent is one of N,N-dimethylformamide, chloroform, acetone, and dimethyl sulfoxide; Step 3, preparation of fluorinated pyridine-type benzoxazine resin friction layer: The dispersion obtained in step 2 is sprayed on the pre-treated copper electrode sheet, and then placed in an oven for gradient temperature curing. After curing, a composite coating is formed on the copper electrode sheet, and the composite coating is a fluorine-containing pyridine-type benzoxazine resin friction layer.

2. The method for preparing a fluorinated pyridine-type benzoxazine resin friction layer for a droplet nanogenerator according to claim 1, characterized in that: In step 1, the molar ratio of 3,5-difluoro-2,6-diaminopyridine, phenol source and paraformaldehyde is (0.5-1.5):(3-5):(4-6).

3. The method for preparing a fluorinated pyridine-type benzoxazine resin friction layer for a droplet nanogenerator according to claim 1, characterized in that: The dosage of the paraformaldehyde and the organic solvent is in the ratio of (0.4-1.2 g): (20-60 mL); the organic solvent is any one of toluene, dioxane, ethyl acetate or chloroform.

4. The method for preparing a fluorinated pyridine-type benzoxazine resin friction layer for a droplet nanogenerator according to claim 1, characterized in that: In step 1, the certain temperature condition is 30-60°C, the stirring time is 1-3h; the reaction time is 3-10h; the alkali washing refers to washing with a NaOH solution with a concentration of 1-3mol / L; the vacuum drying temperature is 80-120°C, and the drying time is 3-8h.

5. The method for preparing a fluorinated pyridine-type benzoxazine resin friction layer for a droplet nanogenerator according to claim 1, characterized in that: In step 2, the mass ratio of the fluorinated pyridine benzoxazine monomer to the two-dimensional carbon nanomaterial is: (50-100): (1-5); the two-dimensional carbon nanomaterial is any one of graphene, graphene oxide, and fluorinated graphene; the amount of the fluorinated pyridine benzoxazine monomer and the solvent is in the ratio of (0.1-0.8 g): (10-30 mL).

6. The method for preparing a fluorine-containing pyridine-type benzoxazine resin friction layer for a droplet nanogenerator according to claim 1, characterized in that: In step 2, the stirring reaction under the certain temperature condition is carried out at a temperature of 20-50° C. and a time of 1-8 h.

7. The method for preparing a fluorine-containing pyridine-type benzoxazine resin friction layer for a droplet nanogenerator according to claim 1, characterized in that: In step 3, the pre-treated copper electrode sheet treatment process is: first use ethanol ultrasonic cleaning for 0.5-2h, and then use a plasma surface treatment instrument to perform surface treatment on the copper electrode sheet for 2-8min.

8. The method for preparing a fluorine-containing pyridine-type benzoxazine resin friction layer for a droplet nanogenerator according to claim 1, characterized in that: In step 3, the gradient curing is as follows: with a gradient of 10-30°C, the treatment is carried out under different gradient temperature conditions, the temperature range is 30°C-170°C; the treatment time under each gradient temperature condition is 1-2h.

9. Use of the fluorine-containing pyridine-type benzoxazine resin friction layer for a droplet nanogenerator prepared by the method according to any one of claims 1 to 8 in preparing a droplet nanogenerator.

10. The use according to claim 9, characterized in that Here are the steps: A copper sheet is used as an electrode sheet; firstly, a fluorinated pyridine-type benzoxazine resin friction layer is pasted on the surface of the electrode sheet, and the friction layer covers the electrode sheet as a whole; then, a copper foil is pasted on a local area of ​​the friction layer to obtain a droplet nanogenerator.